What does frustration, serendipity and uncertainties of global media and communication means? Some versions from Latvia and Estonia - Hanovs , Deniss; Rozukalne, Anda (Information & Media, 2020)
In a short novel by contemporary Russian writer Vladimir Sorokin “White square” (2018), the moderator of the show with the same title gets killed during the show in which four guests express their visions of present society. Everyone can follow the killing on-line, having voted shortly before for the most entertaining guest. After having received an injection of a new chemical formula which is supposed to entertain the audience, the four participants get wild and destroy the whole show enjoyed by the audience. A new moderator is being engaged to let the show go on... This rather gothic plot shows another part of the reality – the memories of the director of the show about someone, a person unknown to the reader, who has been killed to start the bloody entertainment. The ring, made of the skin of this unknown person gets lost and lands in a realm beyond the on-line entertainment culture: poor workers, their uneducated wives and alcoholics, who still inhabit the off-line everyday life of low wages, heavy physical jobs and simple joys ignored by blood thirsty audience, voting and selling advertisement time for higher prices. Both groups, digital media users and poor underpaid blue collars are in contemporary Europe and the USA targets for populist messages in media.